Marjolin Ulcer: An Observational Epidemiological Study From a Tertiary Care Centre in India. Issue 5 (November 2019) - Chaturvedi, Gaurav; Gupta, Ashish Kumar; Das, Saikat; Gohil, Amish Jayantilal; Lamba, Shashank
Abstract : Introduction: Marjolin ulcer is a rare skin malignancy. Marjolin ulcer arises in zones of long-standing scars, inflammation, or chronic wounds. Material and methods: The present study was conducted to assess the demographic profile and identify the predictors of recurrence in 55 patients with Marjolin ulcer admitted over 10 years. Patients underwent either wide local excision with 2-cm peripheral margin or amputation if clinically indicated due to joint involvement. Lymph nodes were dissected if found positive. Patients received adjuvant radiotherapy if tumor clearance was less than 4 mm or the draining lymph nodes were positive. Results: Of the total 55 cases (mean age, 48.75 years; range, 24–74 years), 34 were men and 21 were women (male/female, 1.6:1). The most common cause of injury was flame burn (n = 32, 58%) followed by trauma (n = 10, 18%). The lower limb was frequently affected (n = 38, 69.1%). Twenty-six patients with resection margins less than 4 mm had received adjuvant radiotherapy. Among the 55 patients, 6 (11%) had undergone lymph node dissection. Local recurrence was noted within 18 months in 9 (16.35%) patients, of which 5 patients had a tumor-free margin of less than 4 mm. We found 2 predictors for local recurrence. First, moderately differentiated squamous cell carcinoma ( P = 0.04) and, second, patients with lymph node involvement ( P = 0.001). Conclusion: Marjolin ulcer is a high-risk skin tumor. Patients with positive lymph node or with moderately differentiated squamous cell carcinoma have high chances of recurrence. Frequent and intense follow-up is required for at least 2 years.